The fairy tales of Hermann Hesse - Hesse, Hermann (Bantam Books, 1995)
Merging Eastern mysticism with the motifs of the European fairy tale, the stories translated for this volume, many for the first time, offer insight into Hesse's development as an artist during the first two decades of this century. Sometimes lush and lyrical, sometimes in the simple language of the parable, these tales elaborate Hesse's concerns with mortality, the unity of life and the isolation of the artist. Characters renounce human society to become poets, vegetarians or, as in the fantastic story "Faldum," a mountain. The artist as ascetic, observer and loner, misunderstood by his audience, is a recurring theme.